2015
DOI: 10.1007/s10495-015-1201-6
|View full text |Cite
|
Sign up to set email alerts
|

SOX6 and PDCD4 enhance cardiomyocyte apoptosis through LPS-induced miR-499 inhibition

Abstract: Sepsis-induced cardiac apoptosis is one of the major pathogenic factors in myocardial dysfunction. As it enhances numerous proinflammatory factors, lipopolysaccharide (LPS) is considered the principal mediator in this pathological process. However, the detailed mechanisms involved are unclear. In this study, we attempted to explore the mechanisms involved in LPS-induced cardiomyocyte apoptosis. We found that LPS stimulation inhibited microRNA (miR)-499 expression and thereby upregulated the expression of SOX6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…PDCD4 has been validated as a direct target of miR-21, and it has been reported that miR-21 could protect myocardium against ischemia-induced or H 2 O 2 -induced apoptosis and ischaemia/reperfusion injury through targeting PDCD4 [9, 3233]. In this study, the luciferase report assay also validated that PDCD4 was a direct target of miR-499-5p because ectopic overexpression or inhibition of miR-499-5p increased or decreased the luciferase activities of cardiomyocytes transfected with the wild type PDCD4 3′UTR reporter vector rather than the mutant reporter vector, which is also validated by two recent researches [3435]. Furthermore, the mRNA and protein expression of PDCD4 in cardiomyocytes is able to be modulated by miR-499-5p as detected by both gain-of-function and loss-of-function strategies.…”
Section: Discussionsupporting
confidence: 79%
“…PDCD4 has been validated as a direct target of miR-21, and it has been reported that miR-21 could protect myocardium against ischemia-induced or H 2 O 2 -induced apoptosis and ischaemia/reperfusion injury through targeting PDCD4 [9, 3233]. In this study, the luciferase report assay also validated that PDCD4 was a direct target of miR-499-5p because ectopic overexpression or inhibition of miR-499-5p increased or decreased the luciferase activities of cardiomyocytes transfected with the wild type PDCD4 3′UTR reporter vector rather than the mutant reporter vector, which is also validated by two recent researches [3435]. Furthermore, the mRNA and protein expression of PDCD4 in cardiomyocytes is able to be modulated by miR-499-5p as detected by both gain-of-function and loss-of-function strategies.…”
Section: Discussionsupporting
confidence: 79%
“…This correlates with increased TNF-α production and NF-κB p65 phosphorylation [25]. Investigation of neonatal rat cardiomyocytes demonstrated that LPS inhibited the expression of miR-499, which in turn de-repressed SOX6 and PCDC4 leading to cardiomyocyte apoptosis through activation of the Bcl-2 family apoptotic pathway [111]. …”
Section: Discussionmentioning
confidence: 99%
“…Another high impact study was the investigation of LPS mediated cardiomyocyte apoptosis, which is a mechanism of sepsis-induced cardiac cell death. It was found that LPS stimulation inhibited microRNA (miR)-499 resulting in upregulated expression of the miR-499 target genes SOX6 and PDCD4 and activation of the Bcl-2 family pathway [3]. In a study by Yu et al the effect of melatonin in endoplasmatic reticulum stress was described [4].…”
Section: The Editors’ Choicementioning
confidence: 99%